2008
DOI: 10.1002/jca.20181
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of the outcome of plasma exchange and aggressive medical therapy in antibody mediated rejection of renal allografts: A single center experience

Abstract: Only a shorter interval between transplantation and the acute rejection episode correlated with a good response to PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Debate continues about exact pathologic diagnostic criteria . AMR complicates the course of about 10% of transplants, depending on the rate of pretransplant sensitization of the transplant population . AMR adversely affects long‐term graft function; 1‐year graft survival varies depending on the treatments used, and most grafts that survive are left with decreased renal function .…”
Section: Renal Diseases and Conditions In Children Treated By Apheresismentioning
confidence: 99%
“…Debate continues about exact pathologic diagnostic criteria . AMR complicates the course of about 10% of transplants, depending on the rate of pretransplant sensitization of the transplant population . AMR adversely affects long‐term graft function; 1‐year graft survival varies depending on the treatments used, and most grafts that survive are left with decreased renal function .…”
Section: Renal Diseases and Conditions In Children Treated By Apheresismentioning
confidence: 99%
“…12 Although the role of PLEX has not been confirmed, studies have shown it to be beneficial especially in combination with other agents. 13,14 Other strategies for managing ABMR include the use of rituximab, which targets pre-B cells and B cells, and bortezomib, which is a proteasome inhibitor. 15,16 Uncontrolled randomised studies have shown benefit in both rituximab and bortezomib.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Pretransplant sensitization is indeed a major risk factor for acute antibody-mediated rejection (ABMR) after transplant, with an increased risk of allograft loss. [1][2][3][4] Despite its recognition for .20 years as a defined clinicopathologic entity, [4][5][6][7] treatment strategies for acute biopsyproven ABMR are still not standardized. In general, therapeutic strategies have been based on the removal of antidonor alloantibodies (eg, by series of plasmapheresis or immunoadsorption sessions), associated with attempts to suppress antidonor humoral responses (eg, by using intravenous immunoglobulin [IVIg] or the anti-CD20 monoclonal antibody rituximab).…”
mentioning
confidence: 99%